Divergent regulation of auxin responsive genes in root-knot and cyst nematodes feeding sites formed in Arabidopsis - Patricia Abril-Urias; Virginia Ruiz-Ferrer; Javier Cabrera; Rocio Olmo; Rocio Olmo; Rocio Olmo; Ana Cláudia Silva; Ana Cláudia Silva; Fernando Evaristo Díaz-Manzano; Jose Domínguez-Figueroa; Jose Domínguez-Figueroa; Ángela Martínez-Gómez; et al. (Frontiers in Plant Science, 2023)
Cysts (CNs) and root-knot nematodes (RKNs) induce specialized feeding cells, syncytia, and giant cells (GCs), respectively, within plant roots. The plant tissues around the GCs usually by respond forming a root swelling called a gall that contains the GCs. The ontogenesis of feeding cells is different. GC formation is a process of new organogenesis from vascular cells, which are still not well characterized, that differentiate into GCs. In contrast, syncytia formation involves the fusion of adjacent cells that have already differentiated. Nonetheless, both feeding sites show an auxin maximum pertinent to feeding site formation. However, data on the molecular divergences and similarities between the formation of both feeding sites regarding auxin-responsive genes are still scarce. We studied genes from the auxin transduction pathways that are crucial during gall and lateral root (LR) development in the CN interaction by using promoter-reporter (GUS/LUC)transgenic lines, as well as loss of function lines of Arabidopsis. The promoters pGATA23 and several deletions of pmiR390a were active in syncytia, as were in galls, but pAHP6 or putative up-stream regulators as ARF5/7/19 were not active in syncytia. Additionally, none of these genes seemed to play a key role during cyst nematode establishment in Arabidopsis, as the infection rates in loss of function lines did not show significant differences compared to control Col-0 plants. Furthermore, the presence of only canonical AuxRe elements in their proximal promoter regions is highly correlated with their activation in galls/GCs (AHP6, LBD16), but those promoters active in syncytia (miR390, GATA23) carry AuxRe overlapping core cis-elements for other transcription factor families (i.e., bHLH, bZIP). Strikingly, in silico transcriptomic analysis showed very few genes upregulated by auxins common to those induced in GCs and syncytia, despite the high number of upregulated IAA responsive genes in syncytia and galls. The complex regulation of auxin transduction pathways, where different members of the auxin response factor (ARF) family may interact with other factors, and the differences in auxin sensitivity, as indicated by the lower induction of the DR5 sensor in syncytia than galls, among other factors, may explain the divergent regulation of auxin responsive genes in the two types of nematode feeding sites.